2021
DOI: 10.1016/j.phro.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of radiotherapy deep learning dose prediction models for breast cancer

Abstract: Background and purpose Treatment planning of radiotherapy is a time-consuming and planner dependent process that can be automated by dose prediction models. The purpose of this study was to evaluate the performance of two machine learning models for breast cancer radiotherapy before possible clinical implementation. Materials and methods An in-house developed model, based on U-net architecture, and a contextual atlas regression forest (cARF) model integrated in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…The slice selection was done through Gaussian sampling to select the more important central slices containing the PTVs. The Gaussian scheme had a standard deviation that was equal to one-third of the distance from the central slice to the end slice as previously used by Bakx et al [13] .
Figure 1 Visualization of the Euclidean distance map transformation.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The slice selection was done through Gaussian sampling to select the more important central slices containing the PTVs. The Gaussian scheme had a standard deviation that was equal to one-third of the distance from the central slice to the end slice as previously used by Bakx et al [13] .
Figure 1 Visualization of the Euclidean distance map transformation.
…”
Section: Methodsmentioning
confidence: 99%
“…A schematic representation of the network is shown in Figure 2 . All model parameters were initially a combination of the parameters used by Bakx et al [13] and the HD U-net from Nguyen et al [16] . Different models with varying parameters were tested to find an optimal working model for our particular patient group [17] , [18] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second model was developed by RaySearch and is based on contextual atlas regression forests (cARF)[ 10 ]. A more detailed description of both models and their training on in-house clinical data was previously published by Bakx et al [ 7 ] and can also be found in the Additional file 1 . The current study focused on the clinical applicability of both models.…”
Section: Methodsmentioning
confidence: 99%
“…The dose prediction model can make an end-to-end mapping transformation between patients' anatomical and dose distribution information with organs-atrisk (OARs) constraints (9)(10)(11)(12). Compared with using the conventional treatment planning system (TPS), using the DL model to generate predicted dose distribution reduces planning time significantly (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%